Charts of war the maps and charts that have informed and illustrated war at sea - Blake, John (Conway Maritime, 2006)
"From the ships of small expeditionary fleets, which carried navigational charts, to the requirements of modern ships involved in combined operations, which need charts to include a whole range of information, John Blake has produced an illustrated account of the role that charts have played in planning, preventing, conducting and recording war at sea. The selection not only includes charts depicting major battles and amphibious operations, but those drawn up for tactical and espionage purposes, for coastal defence and the positioning of forts along rivers and at the entrance to harbours." "Chapters run in chronological order, organized according to the overall political scene, but the main focus is on the development of chartmaking and surveying in relation to changing warfare techniques. Informative captions accompany each chart, setting them in historical context and providing details about the main protagonists and the chartmakers and surveyors themselves."--Jacket